MODEL PENGEMBANGAN USAHA INDUSTRI MEBEL MELALUI PENDEKATAN KLUSTER DI KELURAHAN BUKIR KECAMATAN GADINGREJO KOTA - . Sudarti (Jurnal Ekonomi Pembangunan, 2011)
The objective of this research was to decide model of furniture industry development through cluster approach. By taking 49 industries from 103 furniture industry as a sample through purposive sampling technique. Data analysis technique used descriptive qualitative and descriptive quantitative. The results shows that Pasuruan City with the main basis is agricultural sector and the product is household handicraftch which is supported by the sources of facillities in services economic sector that support the activities of society economy and region which are able to develop its potential. The economy activities in furniture field for Pasuruan City was Leading Sector. It showed that furniture handicraft contributed to  the society and for the Pasuruan government income. Besides, it lifted the small and medium industries up which were able to increase the job opportunity for its society.